Concentration of Spermatozoa and The Thickness of The Seminiferous Tubules of Male White Rats After Administration of Moringa Leaf (Moringa oleifera L.) - Sugiantari, Ida Ayu Putu; Suaskara, Ida Bagus Made; Suarni, Ni Made Rai (Metamorfosa: Journal of Biological Sciences, 2020)
Moringa is a plant whose leaf are commonly consumed as vegetables and now moringa leaves are also used as tea and additives in cakes. The results of the study on moringa are still controversial, on the one hand saying moringa can improve the quality of spermatozoa and on the other hand say it can inhibit fertility.The aim of this study was to analyze the effect of moringa leaf steeping on the concentration of spermatozoa and epithelial thickness of seminiferous tubules. A male rat with as many as 24 with weighing 200 g were divided into four treatments namely control (P0), 18 mg / kg BB (P1), 36 mg / kg BB (P2) and 72 mg / kg BB (P3) for 30 days. The results showed that moringa leaves steeping had a significant effect by decreasing the concentration of spermatozoa (P?0.05), moringa leaf steeping has no effect on the epithelial thickness of the seminiferous tubules but causes the germinal epithelium to become loose because many epithelium is loose.